Clinical implications and immune implications features of TARS1 in breast cancer - Gui, Zhengwei; Liu, Piao; Zhang, Dong; Wang, Wanju (Frontiers in Oncology, 2023)
Background：There has been an increase in the number of women suffering from breast cancer in recent years, and discovering new therapeutic targets and efficacy predictive markers is critical for comprehensive breast cancer treatment.Methods ： First, we used bioinformatics methods to analyze TARS1(encoding cytoplasmicthreonyl-tRNA synthetase) expression, prognosis, and clinicopathological characteristics in TCGA database breast cancers, and then we collected breast cancer specimens from our center for validation. TARS1 was then subjected to GSEA (Gene Set Enrichment Analysis) enrichment analysis, GO/KEGG pathway enrichment analysis, and breast cancer immune infiltration characterization. As a last step, we examined TARS1's effects on breast cancer cell behavior with cellular assays.Results: The overexpression of TARS1 has been found in several malignant tumors, including breast cancer, and has been linked to poor prognoses. Breast cancers with large primary tumors and negative hormone receptors are more likely to overexpress TARS1.as Tregs and Th2s, while inhibiting the infiltration of NK cells and CD8+ T cells, which are anticancer cells in breast cancer. TARS1 was also found to be co-expressed with the majority of immune checkpoint-related genes, and breast cancer with TARS1 overexpression responded better to immunotherapy. By knocking down TARS1, breast cancer cells were prevented from proliferating and invading, as well as exhibiting other malignant biological properties.Conclusions：According to our study, TARS1 may be an oncogene in breast cancer and may be a biomarker of efficacy or a target of immunotherapy in breast cancer.